Serum copeptin is a new biomarker of continuous-positive-airway-pressure treatment in severe obstructive sleep apnea. (25th November 2020) - Sekiguchi, H; Ishida, I; Suzuki, M; Hagiwara, M
Abstract: Introduction: Copeptin, the C-terminal fragment of antidiuretic hormone (ADH), is a biomarker which has been reported to be increased in cardiovascular and cerebrovascular diseases, thus playing a role in predicting their prognosis. Patients with obstructive sleep apnea syndrome (OSA) have been demonstrated to have a high risk for developing these vascular diseases. However, there have been no authentic reports concerning the effect of continuous positive airway pressure (CPAP) on serum copeptin levels in OSA patients. Purpose: We hypothesis that CPAP treatment substantially modifies copeptin levels in OSA patients. Methods: A total of 60 OSA patients confirmed by polysomnographic examinations was divided into two groups: a mild-moderate OSA (apnea-hypopnea index: AHI <30/h) group and a severe OSA (AHI ≥30/h) group. Blood samples were collected early in the morning after overnight fasting, and serum copeptin and ADH levels were measured with an enzyme immunoassay method. In patients initiated with CPAP, hormone levels were measured before and after CPAP treatment. Results: Twenty-one patients (age: 54.7±12.4 y, male: 17, NT-proBNP: 45.3±44.2 pg/mL) were diagnosed as having mild-moderate OSA (AHI: 16.5±8.4/h), while 39 patients (age: 57.8±11.4y, male: 29, NT-proBNP: 73.7±87.3 pg/mL) were diagnosed as severe OSA (AHI: 49.5±21.1/h). As a whole, there were no significant differences in copeptin and ADH levels between mild-moderate OSA and severe OSA groups (copeptin: 2.1±1.4 pmol/L vs. 1.9±1.4, ADH: 2.3±2.6 pg/dL vs. 2.0±0.7). In 26 severe OSA patients (age: 55.9±12.9y, male: 23, NT-proBNP: 63.3±85.2 pg/mL), these hormones were again evaluated after CPAP initiation. AHI was significantly improved after CPAP treatment (45.5±20.8/h vs. 5.0±5.0, P<0.01). Although the ADH level was changed from 1.85±0.77 pg/dL to 1.68±0.99, the difference did not reach the statistical significance. The copeptin level was certainly decreased after CPAP by 26% (2.29±2.63 pmol/L vs. 1.69±1.68, P<0.01) (Figure 1). Conclusions: Serum copeptin levels decreased after CPAP treatment in patients with severe OSA. Copeptin, but not ADH, can be considered as a new biomarker for predicting cardio/cerebrovascular events in severe OSA patients. Funding Acknowledgement: Type of funding source: None